2013
DOI: 10.2214/ajr.12.9202
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Cysts: Natural History by Long-Term Imaging Follow-Up

Abstract: Interval enlargement of an adrenal cyst is frequent and as an isolated finding does not indicate malignancy or presence of a complication. However, some adrenal cysts may decrease or remain stable in size over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 40 publications
1
17
0
4
Order By: Relevance
“…There is no predilection for the right versus left gland, and bilateral cysts are present in approximately 15% of cases (34). These cysts can range in size from less than a centimeter to greater than 20 cm (32-34), although most are small to medium-sized, with one recent study reporting median and mean baseline sizes of 4.2 cm and 5.3 cm, respectively (35).…”
Section: Adrenal Cystsmentioning
confidence: 99%
“…There is no predilection for the right versus left gland, and bilateral cysts are present in approximately 15% of cases (34). These cysts can range in size from less than a centimeter to greater than 20 cm (32-34), although most are small to medium-sized, with one recent study reporting median and mean baseline sizes of 4.2 cm and 5.3 cm, respectively (35).…”
Section: Adrenal Cystsmentioning
confidence: 99%
“…Además, del potencial de malignización, se han reportado otras indicaciones quirúrgicas en QA no funcionales, incluyendo: el crecimiento del QA, la hemorragia con colapso cardiovascular, la ruptura quística, o el compromiso de órganos vecinos con incertidumbre etiológica 1,2,[13][14][15] . En este caso se descartó funcionalidad, hubo crecimiento quístico, hallazgos de complejidad e incertidumbre etiológica con sospecha de compromiso renal, que no se aclaró con imágenes (ecografía, TC de abdomen y ecoendoscopia), por lo que se resecó.…”
Section: Discussionunclassified
“…La historia natural del QA ha sido pobremente reportada en la literatura y la información es escasa en términos de manejo definitivo 2 . Es aceptado que para el correcto abordaje del QA, se requiere dife-Figura 1. evolución escanográfica del quiste adrenal (Qa) en un periodo de 34 meses.…”
Section: Introductionunclassified
“…In a series of 20 patients, Ricci et al 12 reported that lesion enlargement was actually a frequent finding on follow-up and as an isolated manifestation should not be considered as suspicious for malignancy.…”
Section: Discussionmentioning
confidence: 99%